2000
DOI: 10.1016/s0014-5793(00)02029-9
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of yeast tRNAPhe with complementary oligonucleotide conjugated to a small ribonuclease mimic

Abstract: An oligonucleotide conjugate bearing a chemical construct mimicking the catalytic center of ribonuclease A has been designed and studied. The conjugate efficiently cleaves yeast tRNA Phe at a single site adjacent to the target complementary sequence. ß

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Over the last couple of decades, some progress has been achieved in the field of designing siteselective artificial ribonucleases [42][43][44][45][46][47][48][49][50][51][52][53][54]. It was shown that short peptides, containing either alternating leucine and arginine residues or imidazole-based catalytic groups, conjugated to antisense oligonucleotides targeting tRNA, were able to hydrolyze linkages adjacent to an oligonucleotide-binding site without involvement of exogenous species such as metal ions, enzymes or cofactors (e.g., RISC, RNase H) [42,44,45,47,50,51].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last couple of decades, some progress has been achieved in the field of designing siteselective artificial ribonucleases [42][43][44][45][46][47][48][49][50][51][52][53][54]. It was shown that short peptides, containing either alternating leucine and arginine residues or imidazole-based catalytic groups, conjugated to antisense oligonucleotides targeting tRNA, were able to hydrolyze linkages adjacent to an oligonucleotide-binding site without involvement of exogenous species such as metal ions, enzymes or cofactors (e.g., RISC, RNase H) [42,44,45,47,50,51].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…It was shown that short peptides, containing either alternating leucine and arginine residues or imidazole-based catalytic groups, conjugated to antisense oligonucleotides targeting tRNA, were able to hydrolyze linkages adjacent to an oligonucleotide-binding site without involvement of exogenous species such as metal ions, enzymes or cofactors (e.g., RISC, RNase H) [42,44,45,47,50,51]. Effective cleavage of complementary substrates was also demonstrated for tris(2-aminobenzimidazole) ribonuclease conjugated to PNA oligomers [49].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Particularly encouraging is the near-optimal cleavage at low concentrations (0.5 mM) of di-imidazole lexitropsin. This is slightly lower than previous imidazole-based artificial nucleases (8,12), with the exception of antisense-imidazole conjugates (13,14). However, while previous imidzole-based RNase mimics contain ligands that were specifically designed for RNA binding, this is not so for diimidazole lexitropsin.…”
Section: Specificity and Efficiency Of Cleavagementioning
confidence: 76%
“…Ligands tested so far ( Fig. 1) include intercalating agents (12), lysine (8), polyamines (11), antisense oligonucleotides (13,14), and others (reviewed in 8).…”
mentioning
confidence: 99%
“…We recently used an L-homoserine linker for this purpose to provide a general and convenient procedure for the preparation of oligonucleotides conjugated at the 3'-end to a range of reporter groups and short peptides such as Lys, (6). His-functionalized oligonucleotides may be useful as potential ribonuclease mimics (9). Thus starting with solid support (LCAA-CPG-500) containing a spacer unit and N-a-Fmoc-O-trityl-L-homoserine (Scheme), 1, 2 or 3 /V m -Boc histidyl residues were coupled by standard peptide synthesis (96% and 94% yields for m=2 and m=3 respectively), with acetic anhydride capping after each step.…”
Section: Resultsmentioning
confidence: 99%